Narrativas transmídias e apropriações de letramentos digitais e literários por crianças : contribuições para as práticas pedagógicas de professores e pesquisas acadêmicas - Paula, Marta da Conceição de (2021)
This Master's dissertation entitled “Transmedia Narratives and Appropriations of Digital and Literary Literacy by Children: Contributions to the Teachers Pedagogical Practices and academic research” is inserted in the Post Graduate Program in Education (PPGE), of the Federal University of Mato Grosso (UFMT), in the research line School Organization, Training and Pedagogical Practices, within the Research Group Laboratory of Studies on Information and Communication Technologies in Education (LêTECE). The study aims to understand the appropriations of Digital and Literary Literacy mobilized in transmedia narratives by children in order to reflect about contributions of that appropriations to the literary pedagogical practices of teachers and academic research. The research was developed through the Research-Formation methodology, and its field was the online teaching of the teacher/researcher in a WhatsApp group known as “Digital Literature”, with three children from 4th grade (9 years old) of the City School of Basic Education Senhorinha Ana Alves de Oliveira, in Cuiabá City - MT. The research-formation engendered an ethnography in cyberculture with the mapping of literary channels on YouTube, survey of a collection of children's literary works and creation of a research-formation device for the transmediation of the children work “The world in Tayó's black power” involving various networked digital technologies, with the literary literacy methodology for the various stages of transmedia, culminating in the production of digital textual genres such as comic book, meme, animation and video research-formation entitled: “Narratives Transmedia with children”. Records of the research paths and processes were kept in an online diary. The research findings indicate that literary transmedia mobilizes multiple dimensions of literacy in the children and the teacher/researcher, among them the transmedia that emerges as an unfolding of digital and literary literacy mobilized by the children, which presents the following contributions to pedagogical practices: criticality in relation to important social issues in contemporary culture, expansion of linguistic, literary, and cultural competencies, reflections on the use of networked digital technologies, and the way research-formation in cyberculture is constituted in this study contributes to other academic research. Digital and Literary Literacy in contemporary culture are characterized by the complexities surrounding social practices and are therefore different in each cultural context. This raises new reflections regarding its implications for pedagogical practices in the classroom and its unfolding in the school.